Principles and practice of structural equation modeling - Kline, Rex B. (Guilford Press, 2016)
Emphasizing concepts and rationale over mathematical minutiae, this is the most widely used, complete, and accessible structural equation modeling (SEM) text. Continuing the tradition of using real data examples from a variety of disciplines, the significantly revised fourth edition incorporates recent developments such as Pearl's graphing theory and the structural causal model (SCM), measurement invariance, and more. Readers gain a comprehensive understanding of all phases of SEM, from data collection and screening to the interpretation and reporting of the results.- Resumé vydavatel
Keywords: statistické metody; vícerozměrné statistické metody; statistické modely; společenské vědy -- metodologie; statistical methods; multivariate analysis; statistical models; social sciences -- methodology; structural equation models (SEM); elektronické knihy; monografie; electronic books; monographs